Faktor-faktor yang mempengaruhi perilaku masyarakat meningkatkan kualitas lingkungan pada Wilayah pesisir kabupaten maros - Faizal Amir; Muhammad Ardi; Bakhrani A. Rauf (Seminar Nasional LP2M UNM, 2019)
The purpose of this study was to find out the influence of ecosystem knowledge, environmental conservation knowledge, environmental knowledge, motivation to preserve the environment, and environmental environment both individually and collectively on community behavior to improve environmental quality in the coastal areas of Maros Regency. The variables that are considered in this study are the dependent variable that is people's behavior to improve the quality of the environment of the coastal area (Y) and the independent variables are: (a) knowledge of coastal ecosystems (X1); (b) knowledge of environmental conservation (X2); (c) environmental knowledge (X3); (d) motivation to maintain the environment (X4); and (e) Attitudes towards the environment of coastal areas (X5). The analysis used is descriptive statistical analysis and statistical statistical analysis. The analysis model used is simple regression and multiple regression. The results of the study are as follows: (1) people's behavior in improving the quality of the environment in the coastal area of Maros Regency is classified as moderate. (2) knowledge of ecosystems, conservation knowledge, environmental knowledge, motivation to maintain the environment, and attitudes towards the environment of the community in the coastal area of Maros Regency are classified as moderate, influential both individually, and jointly on community behavior to improve the quality of the environment in the region the coast of Maros Regency